Formation of dendrimer-guest complexes as a strategy to increase the solubility of a phenazine N, N′-dioxide derivative with antitumor activity - Dib, Nahir; Fernández, Luciana; Santo, Marisa; Otero, Luis; Alustiza, Fabrisio Eduardo; Liaudat, Ana Cecilia; Bosch, Pablo; Lavaggi, María Laura; Cerecetto, Hugo; González, Mercedes Florencia (Elsevier, 2019)
Poly(amidoamine) and Poly(propylenimine) dendrimers with different generations and peripheral groups were studied as solubility enhancers and nanocarriers for 7-bromo-2-hydroxy-phenazine N5,N10-dioxide. This compound possesses potential antitumoral and anti-trypanosomal activity, but its low solubility in physiological media precludes its possible application as therapeutic drug. The amino terminated dendrimers association with the active compounds as observed trough NMR studies showed that electrostatic interactions are essential in the solubilization enhancement process. The obtaining of a stable and no cytotoxic formulation makes the drug-carried association a suitable strategy for the generation of a drug delivery system for phenazine derivatives.